Soil, fodder and serum mineral (cattle) and haematobiochemical profile in somedistricts of Central Uttar Pradesh - SHARMA, M C; JOSHI, CHINMAY; DAS, GUNJAN (The Indian Journal of Animal Sciences, 2011)
To record the mineral, hormone and vitamin status in cattle of some districts of Central Uttar Pradesh a survey was conducted. It was observed, that the macro minerals mainly calcium (Ca), magnesium (Mg) and phosphorus (P) were deficient and well below the critical level, along with significant deficiency in micro minerals, viz. copper (Cu) and zinc (Zn). The soil-fodder and serum status of all these districts was significantly co-related at 1% and 5% level. Significant decrease was observed in haemoglobin (Hb), and total erythrocyte count (TEC) while total leukocyte count (TLC) was slightly higher in deficient cattle. The values of serum enzymes, viz. aaspartate transaminase (AST) and, aalanine transaminase (ALT) were lower whereas serum alkaline phosphatase (SAP) was higher. The values of thyroid hormones (T3 and T4) and vitamins (A and E) were significantly lower in deficient animals.